MIGRATION OF KOSOVO IN INTERNATIONAL DATABASES: THE PARADOX OF TERRITORIAL STATISTICS IN A TRANSNATIONAL SOCIETY (Heritage, 2026)
Migration from Kosovo represents a distinctive demographic and socio-economic process of the contemporary period. This paper examines which territorially based statistical indicators can adequately describe societies characterized by intensive migration and large diaspora populations. The study analyzes the relationship between the population residing on the territory and the population living abroad by combining several migration indicators. The research is based on a secondary analysis of international statistical databases and includes data on asylum applications in European Union countries, the size of the diaspora, the volume of remittances, and overall population figures.The results indicate several important patterns. First, the existence of a large diaspora and its geographical concentration suggests the presence of stable migration networks and long-established migration routes. Second, the dynamics of asylum applications reveal a wave-like character of migration flows, while simultaneously indicating the persistence of continuous mobility channels. Third, the growing volume of remittances confirms strong economic ties between the diaspora and the society of origin. Taken together, these findings demonstrate that social and economic processes related to Kosovo do not occur exclusively within territorial borders, but rather unfold within a broader transnational space that encompasses diaspora populations. In this context, the diaspora appears not merely as a consequence of migration but as a structural demographic and economic component of society.The analysis also highlights the limitations of classical statistical approaches. Since most demographic and economic statistics are organized around territorial categories, they provide only a partial picture of societies shaped by long-term migration. Statistical systems record a specific model of migration, whereas societies experience migration as a complex, transnational reality. When a significant share of the population lives abroad, territorial statistics become less capable of capturing the actual structure of society. Consequently, understanding such processes requires combining multiple indicators and examining the relationship between territorial populations and diasporic communities.
Keywords: migration, diaspora, remittances, transnational space, Kosovo